Investigating Tendencies of Malaysian Muslims in Islamic Estate Planning: Insight into Its Determinants - Norazlina Abd Wahab; Selamah Maamor; Suraiya Hashim; Zairy Zainol; Hakimah Yaacob (USIM Press, 2024)
JMIFR Vol.18 No. 2 (Dec) 2021